Modifikasi Prototipe Robot Pelontar Pakan Ikan dan Sistem Monitoring Level Air pada Tambak - Muslimah Widyaningrum; Gusti Rangga; Abdul Kadir Muhammad; Mukhtar Mukhtar (Jurnal Teknik Mesin Sinergi, 2022)
Fisheries are one of the sectors that are relied upon for national development. In 2019, the export value of Indonesian fishery products reached Rp. 73,681,883,000, which is an increase of 10.1% from 2018 exports. Marine products such as shrimp, tuna, squid, octopus, crabs and seaweed are sought-after commodities. The development of fish farming can be carried out if the availability of good quality seeds and available in sufficient quantities, proper feed, prevention and treatment of disease and a good living environment. The survival rate at the seed stage is influenced by the type of feed given and the amount according to the needs of the fish. This study aims to modify the previous feed throwing robot so that it can be thrown further and the feed is not destroyed so that it can help the work of fish pond farmers in providing fish feed, modify the tool to help fish pond farmers work in knowing the pond water level, design and build a filling system. manually and automatically using solar panels and modifying the information system on the previous tool so that it can display more information to fish pond farmers. The results showed that the ideal distance of feed throw 5.1 meters, and maximum charging using solar panels 14.28 Watts per hour. The feeding system, water level regulator, information system and charging system can facilitate the pond management process